Application of BIM for maintenance and management of academic facilities in the USA: a review. (2016) - Phillips, Samuel B.; Azhar, Salman; Khalfan, Malik M.A.
The purpose of this paper is to analyse the feasibility of adopting Building Information Modelling (BIM) for Facility Management (FM) in academic institutions. The study investigated the use of BIM for FM and determined if universities' facilities division can use this emerging technology for periodic and preventive maintenance. A total of four case study universities were selected for review that have considered implementing or were already benefitting from the use of BIM to aid in FM. The case studies were analysed using qualitative content analysis techniques during the review. It was found through the case study analysis that there are different ways in which BIM can be applied to FM within academic sector; each university's focuses, and systems used, were unique to the individual university. A critical analysis was performed, which resulted in the creation of a matrix that compares the four case study universities based on several key parameters.